2013
DOI: 10.1096/fasebj.27.1_supplement.lb686
|View full text |Cite
|
Sign up to set email alerts
|

Shortened life span in mice generated by in vitro fertilization

Abstract: In humans assisted reproductive technologies (ART) induce generalized vascular dysfunction in children. In line with this observation, ART induces vascular dysfunction and arterial hypertension in mice that is related to an epigenetic mechanism, but the long term consequences are unknown. To address this problem, we compared the long term survival of ART and control mice fed a normal chow diet (NC) or challenged with a high‐fat diet (HFD).80 male FVB mice generated by ART and 80 control mice born and raised in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another work, Sherrer's team found that increased methylation on the promoter of the eNOS gene led to a reduction of NO levels in plasma. This increased blood pressure and vascular dysfunction and caused a shorter lifespan in mice born following ART procedures in mothers exposed to a high-fat diet [207]. Even if epigenetic changes occurring during high glucose stress or hypoxia are still under evaluation, evidence links them to eNOS dysfunction.…”
Section: The Role Of Hypoxia and Reactive Oxygen Species On Cardiomyocytesmentioning
confidence: 99%
“…In another work, Sherrer's team found that increased methylation on the promoter of the eNOS gene led to a reduction of NO levels in plasma. This increased blood pressure and vascular dysfunction and caused a shorter lifespan in mice born following ART procedures in mothers exposed to a high-fat diet [207]. Even if epigenetic changes occurring during high glucose stress or hypoxia are still under evaluation, evidence links them to eNOS dysfunction.…”
Section: The Role Of Hypoxia and Reactive Oxygen Species On Cardiomyocytesmentioning
confidence: 99%